Maternal and lactogenic immunity in gestating sows induced by adenoviruses expressing mucosal immunogens derived from porcine epidemic diarrhea virus - Namphueng Butkhot; Thotsapol Kaewchomphunuch; Pimploy Rattanaamnuaychai; Kanokporn Polyiam; Panida Chanapiwat; Natharin Ngamwongsatit; Yaowaluck Maprang Roshorm; Kampon Kaeoket (Animal Diseases)
Abstract Porcine epidemic diarrhea virus (PEDV) is a significant pathogen that causes severe diarrhea and high mortality rates in piglets. Thus, maternal and lactogenic immunity is a key success in protecting piglets from PEDV. Here, we developed four recombinant adenovirus (rAd)-based vaccine candidates against PEDV harboring novel immunogens fused with mucosal adjuvants and evaluated their capacity to elicit maternal and lactogenic immunity in gestating sows. The rAd-based vaccines were developed on the basis of the new immunogen PEDVSME (rAd. PEDVSME) and its derivatives fused with three mucosal adjuvants: bacterial outer membrane protein H (OmpH), cholera toxin B subunit (CTB), and GM-CSF/IL-4 fusion protein (GI). In a randomized controlled trial, a total of 50 pregnant sows (n = 10/group) received a prime-boost vaccination regimen of rAd. PEDVSME, rAd. PEDVSME-OmpH, rAd. PEDVSME-CTB, rAd. PEDVSME-GI and PBS were used as controls. After the second dose, the rAd. PEDVSME-CTB induced the highest PEDV-specific IgG response with the highest PEDV-neutralizing titer in pregnant sows, whereas rAd. PEDVSME-OmpH elicited the greatest level of systemic PEDV-specific IgA responses. For the transfer of maternal PEDV-specific antibodies into colostrum, all three rAd-based vaccines expressing adjuvanted immunogens (PEDVSME-OmpH, PEDVSME-CTB, PEDVSME-GI) were superior to the rAd expressing the original immunogen PEDVSME and the PBS control. Interestingly, IgG was the dominant isotype in colostrum, and correlated more strongly with neutralizing activity than IgA. In offspring, newborn piglets from all four groups of sows receiving rAd-based vaccines had antibodies with neutralizing titers higher than those from the control group. During the weaning period, decreases in neutralizing titers were observed in all groups, except for piglets from the rAd group. PEDVSME-OmpH group, whose neutralizing titers were well maintained and significantly greater than those in the control group (P<0.05). These findings demonstrate that the rAd-based vaccines expressing the PEDVSME immunogen fused with the mucosal adjuvant OmpH (rAd. PEDVSME-OmpH) are primary candidates for further evaluation viral challenge in piglets to determine their protective efficacy via passively lactogenic immunity.